Efektivitas Berbagai Ketebalan Media Arang Aktif Sekam Padi dan Tempurung Kelapa untuk Menurunkan Kadar Chemical Oxygen Demand (COD) Limbah Cair Sablon - Andani, Maulina Dwi; Suwerda, Bambang; Mulyaningsih, Tri; Rois, Ibnu (Jurnal Kesehatan Lingkungan Mandiri, 2025)
Screen printing liquid waste contains heavy metals, high organic matter, and various pollutants such as ammonia and color that can endanger environmental stability if not managed properly. The results of the examination of the quality of Harno Screen Printing liquid waste in Moyudan obtained a Chemical Oxygen Demand (COD) level exceeding the quality standard of 1,069 mg/L. This study aims to determine the effectiveness of various thicknesses of rice husk and coconut shell activated charcoal media in reducing COD levels of Harno Screen Printing Industry liquid waste in Moyudan. The research method is Pre test - Post test with Control Group Design with pre-treatment (coagulation and sedimentation) followed by filtration and adsorption using variations in the thickness of rice husk and coconut shell activated charcoal media of 25 cm: 75 cm, 50 cm: 50 cm, and 75 cm: 25 cm. The reduction in COD after pre-treatment was 96.7%. The average COD reduction after filtration with a thickness of 25 cm: 75 cm was 40.45%, a thickness of 50 cm: 50 cm was 34.16%, a thickness of 75 cm: 25 cm was 71.4%, and a control of 6.93%. Conclusion, Activated charcoal filtration of rice husks and coconut shells 75 cm: 25 cm is the most effective thickness to reduce COD levels in Harno Screen Printing Industry liquid waste with a reduction of 71.4%.